Microwave-assisted from synthesis of 2-arylamino-2-imidazolines on a solid support - Genc, M; Servi, S (Wiley-Blackwell, 2005)
An efficient synthesis of 2-arylamino-2-imidazolines from dimethyl N-aryldithioimidocarbonates and ethylenediamine on solid support under microwave irradiation has been developed. The reaction time has been reduced from hours to minutes with improved yields as compared to conventional heating. Their piperidin-4-ylmethyl and morpholin4-ylmethyl derivatives were synthesized by treatment with formaldehyde and piperidine or morpholine. (c) 2005 Wiley Periodicals, Inc. Heteroatom Chem 16:142-147, 2005; Published online in Wiley InterScience.
Keywords: Diheterocyclic Compounds; Pharmacological-Activity; Derivatives Thereof; Molecular-Structure; Organic-Synthesis; Tautomerism; Systems; Agonist